Seismostratigraphy and geomorphology of the Rio Grande cone, Pelotas basin (Brazilian offshore) (2014)
The Rio Grande Cone feature is a large subsurface structure in the Pelotas Basin located on Brazilian Offshore. Using seismic line grids and well log information, we present a model of the Rio Grande Cone that integrates sequential stratigraphy and geophysical parameters, i.e.; velocity function, system tracts, geomorphic features. The geophysical and stratigraphical model from the Rio Grande Cone establish certain geomorphic features and identify various sequences. This integration enables interpretation of geomorphologic elements (channels, canyons, levees, contourites, fluid escapes and pockmarks), and provides the sequence and geological information needed to build a three-dimensional model from velocity model.